Dampak Negatif Modernisasi dalam Pendidikan - Liqa Fadhila; Firman Firman; Riska Ahmad (Universitas Islam Sumatera Utara, 2022)
Progress that is increasingly undeniable in the world of technology in the era of the industrial revolution 5.0, is increasingly creating changes especially in the culture that is passed through the educational process, called modernization. with the relationship between modernization and education, of course, it also has good and bad impacts, especially on students who are the main figures in education. the focus in this research is how modernization has a bad impact on education. traced through library research. library research is a research conducted using literature. the results of the study found that there were many negative impacts of modernization on education. for example like internet addiction, students no longer rely on teachers and others. That's why the role of the teacher/counseling teacher is needed to guide students so they can minimize these impacts. as well as assistance from all parties and also parents